High-density effects due to interaction of self-trapped exciton with (Ba, 5p) core hole in BaF₂ at low temperature - Terekhin, M.A.; Svechnikov, N.Yu.; Tanaka, S.; Hirose, S.; Kamada, M. (Физика низких температур, 1997)
The effect of VUV undulator excitation intensity on the emission shape and decay time of BaF₂ crystal at low temperature has been observed. The findings are explained in terms of quenching of Auger-free luminescence (cross luminescence) by self-trapped exciton via Förster mechanism energy transfer.